Upaya Meningkatkan Karakter Religiusitas Siswa Kelas I Sekolah Dasar melalui Habit for Me - Aulia Putri; Ibnu Muthi (Jurnal Pendidikan Dirgantara, 2025)
This study employs a qualitative approach with a case study design to gain an in-depth understanding of the implementation of the “Habit for Me” religious habituation program in shaping the religious character of first-grade elementary school students. The case study method was chosen to holistically and contextually describe the phenomenon within the specific school environment. Primary data were collected through participatory observation of students, in-depth interviews with teachers and the principal, and documentation of students' religious activities. Secondary data included lesson plans, religious activity schedules, and school archives to complement the primary data. The diverse data collection techniques aimed to produce credible data. Data analysis was conducted using the Miles and Huberman interactive model, which involves data reduction, data display, and conclusion drawing to derive meaning from complex information. Data validity was ensured through triangulation of techniques and sources, enhancing the trustworthiness of the findings. This methodology enabled a detailed depiction of the processes and impacts of the Habit for Me program in the context of religious character education for elementary students.